Information And Communication Technology (Ict) As Aids In Foreign Languages Teaching (2016)
The aim of the research was to determine if the use of ICT, specifically web 2.0 tools, had an impact on oral skills, it means listening and speaking competences in English as a foreign language. This research was carried out with a population sample of students of the program of modern languages of the University of Quindío. The results were: 1) the ICT helped remarkably improve the oral skills of a second language. 2) Students successfully developed in front of the use of ICT. 3) The tools related to web 2.0 used by the teacher were relevant and appropriate for the teaching of English as a foreign language.